TCP - Barakat, C. (IEEE Network : the magazine of global information exchange)
We discuss the different issues to be considered when modeling the TCP protocol in a real environment. The discussion is based on measurements we made over the Internet. We show that the Internet is so heterogeneous that a simplistic assumption about TCP congestion control or the network may lead to erroneous results. We outline some of our results in this field, and we present a novel approach For a correct validation of a model for TCP